EFEK PENGENCERAN PAKAN DENGAN BUNGKIL KELAPA TERHADAP BERAT KARKAS DAN BERAT LEMAK ABDOMINAL AYAM BROILER FASE AKHIR - Elias Yanto Jorho; Nonok Supartini (BUANA SAINS, 2006)
This research was aimed to describe effect dilution of feed BR2 with coconut oil cake on consumption, accretion of body weight and feed conversion ratio of broiler of finisher period produced by PT. Multi Breeder Adirama Indonesia. Four treatments of dilution of feed BR2 with coconut oil cake with proportions of 80:20, 60:40 , 40: 60, and 20 : 80 and one control (no added coconut oil cake), were arranged in a Completely Randomized Design with four replicates. Variable measured were feed consumption, accretion of body weight, and feed conversion. Results of this research showed that the higher proportion of coconut oil cake used as a feed dilution of finisher period broiler the lower was the carcase and abdominal weight